Intraoperative brief electrical stimulation (BES) for prevention of shoulder dysfunction after oncologic neck dissection: study protocol for a randomized controlled trial - Barber, Brittany (Trials, 2015)
BACKGROUND: Shoulder pain and dysfunction are common after oncologic neck dissection for head and neck cancer (HNC), due to traction, compression, and devascularization injuries to the spinal accessory nerve (SAN). Shoulder pain and dysfunction can hinder postoperative rehabilitation and hygiene, activities of daily living (ADLs), and return to work after treatment for HNC. Due to the rising incidence of human papillomavirus (HPV)-associated oropharyngeal cancer, patients are often diagnosed in the third or fourth decade of life, leaving many potential working years lost if shoulder dysfunction occurs. Brief electrical stimulation (BES) is a novel technique that has been shown to enhance and accelerate neuronal regeneration after injury through a brain-derived neurotrophic growth factor (BDNF)-driven molecular pathway in multiple peripheral nerves in both humans and animals. METHODS/DESIGN: This is a randomized controlled trial testing the effect of intraoperative BES on postoperative shoulder pain and dysfunction. All adult participants with a new diagnosis of HNC undergoing surgery with neck dissection, including Level IIb and postoperative radiotherapy, will be enrolled. Participants will undergo intraoperative BES after completion of neck dissection for 60 min continuously at 20 Hz, 3 to 5 V, in 100-msec pulses. Postoperatively, participants will be evaluated using the Constant-Murley Shoulder Score, a scale that assesses shoulder pain, ADLs, strength, and range of motion. Secondary outcomes measured will include nerve conduction studies (NCS) and electromyographic (EMG) studies, as well as scores on the Oxford Shoulder Score (OSS), the Neck Dissection Impairment Index (NDII), and the University of Washington Quality of Life (UW-QOL) score. Primary and secondary outcomes will be assessed at 6 weeks, 3 months, 6 months, and 12 months. DISCUSSION: The objective of this study is to evaluate the effect of BES on postoperative clinical and objective shoulder functional outcomes and pain after oncologic neck dissection. BES has been shown to be successful in accelerating peripheral nerve regeneration in both animal and human participants in multiple different peripheral nerves. If successful, this technique may provide an adjunctive prevention option for shoulder pain and dysfunction in HNC patients. TRIAL REGISTRATION: NCT02268344: 17 October 2014.